Analisis Kinerja Keuangan Daerah Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun Anggaran 2013-2017 - Sahara, Gabby Febryanti; Muzdalifah (PPJP ULM, 2019)
The aim research (1) to know local financial performance with ratio of fiscaldecentralization degree, local financial independent, effectiveness of PAD, local financeefficiencey and growth PAD regencies/municipalities in South Borneo province 2013-2017,(2) to know business sector which contributed in PDRB. Technical analysis data is descriptifanalysis. The result research showed : by average fiscal decentralization degree ratio 9regencies still very less and 4 regencies/cities less, 7 regencies low, average local financialindependence 4 regencies still very low, 7 regencies low and 2 municipalities enoughindependence, average effectivene PAD ratio almost all of regencies/municipalities veryeffective except Banjarmasin municipality are effective, average local financial efficiencyratio 9 regencies/municipalities less effecient and 2 regencies enough efficient, whileBanjarbaru municipalities inefficient, growth PAD ratio is positive.